"A Catharsis for Anxieties": Insights from Goffman on the Politics of Humour. Issue 1 (2nd January 2021) - Steele, Brent J.
ABSTRACT: Sociologist Erving Goffman's work has increasingly made an impact in International Relations. This paper consults Erving Goffman's work and scholarly sensibility for insights into humour. Sociologists have begun to reconsider Goffman for such purposes, and I draw out three contributions from his studies for our special issue theme. First, Goffman's dramaturgical approach proves useful for understanding the performative aspects of humour and how those might be drawn out in both "high politics" and everyday settings of international relations. Second, Goffman's engagement of jokes and embarrassment proves useful for drawing out the power dynamics of humour. The third contribution of Goffman's work is that it can also serve as a model for the vocational possibilities of humour for the social scientist. I conclude with several Goffmanian "venues" where scholars might and indeed do engage in tension-relieving humour, with the hope that those might be reinforced, protected, and enlivened in the years to come.